Mind + Machine - Marc Vollenweider (Wiley, 2017)
"Mind+Machine is a thought-provoking exploration of data analytics as they stand now. Marc introduces and develops several game-changing concepts, like the Efficient Frontier, Ring of Knowledge, and Use Case Methodology, showing how to apply them for the best possible return on investment. These ideas should be the cornerstone of every organization's approach to data analytics. Written for the generalist with plenty of real-world examples, it's a fascinating read that I couldn't put down."